Strong Contrast in Remote Black Carbon Aerosol Loadings Between the Atlantic and Pacific Basins. Issue 23 (4th December 2018) - Katich, Joseph M.; Samset, B. H.; Bui, T. Paul; Dollner, M.; Froyd, K. D.; Campuzano‐Jost, P.; Nault, B. A.; Schroder, J. C.; Weinzierl, B.; Schwarz, J. P.
Abstract: Measurements of black carbon (BC) aerosol mass concentration in remote air are sparse, leading to poorly constrained regions that models struggle to represent. Here we present a new data set of BC concentration over the remote Pacific and Atlantic basins from 80 N to 65°S latitude that was obtained as part of NASA's Atmospheric Tomography campaign in July/August 2016. More than 100 vertical profiles, extending from 0.2 to 13 km altitude above mean sea level, reveal sharp contrasts in loadings between the two basins. Over the Pacific, we found average BC concentration vertical profiles to be largely consistent with seasonally matched data obtained in 2011. Substantially higher loads were observed over the Atlantic in the low to middle troposphere than in the Pacific, likely due to strong regional sources and reduced convective removal in the tropics in this basin. Atlantic and Pacific BC concentrations converge in the upper troposphere and lower stratosphere, reflecting similar high‐altitude background concentrations. Comparison of the Atlantic data to the Aerosol Comparisons between Observations and Models suite of models (Phase II) reinforces previous speculation about the ensemble in the remote by quantifying an upper‐troposphere model‐high‐bias of as much as two orders of magnitude over wide latitude bands. However, these direct BC measurements reveal Aerosol Comparisons between Observations and Models ensemble underestimation of biomass burning BC in the outflow of continental Africa by nearly a factor of 5. This high‐BC loading region likely dominates BC's direct radiative effect over remote areas of the Pacific and Atlantic basins during the month of August. Key Points: Black carbon loadings over the remote Atlantic are generally comparable to those over the Pacific, except at low-altitude near the equator AeroCom's model‐ensemble average overestimates loadings, except in the lower troposphere of the equatorial Atlantic region The direct radiative effect of BC over the remote Pacific and Atlantic in August is likely dominated by African biomass burning outflow